Lived experience of being a grandparent in one region of Spain: a qualitative study - Sofia García-Sanjuán; Sofia García-Sanjuán; Ana Isabel Gutiérrez-García; Ana Isabel Gutiérrez-García; María José Cabañero-Martínez; María José Cabañero-Martínez; Manuel Fernández-Alcántara; Maria del Carmen Rocamora-Rodriguez; Maria del Carmen Rocamora-Rodriguez; Silvia Escribano; Silvia Escribano (Frontiers Media S.A., 2024)
BackgroundThe evolution of the family model in Europe in the 21st century, and particularly in Spain, has led to grandparents playing a major role in caring for their grandchildren. Grandparents are required to take on certain functions and roles in order to provide this care. This results in changes to their daily lives, their family relationships and therefore their quality of life.ObjectiveTo explore grandparents' lived experience of being involved in the upbringing and care of grandchildren and to determine how this affects their quality of life.MethodologyA descriptive qualitative design was used. The data collection strategy involved two focus groups in two health centres in the province of Alicante (Spain), which were attended by 19 grandparents. Thematic analysis was used to analyse the data.ResultsFour themes and their respective sub-themes emerged from the data analysis: (1) Not only caring, but also raising (implications for upbringing; dealing with their children's rules; nutrition of grandchildren); (2) Motivation for providing care (it is what families do; financial support; barriers to caregiving that outweigh the reasons for caregiving); (3) Significance of gender (grandmothers bring up, grandfathers help out; cultural burden of caregiving for women) and (4) Implications of care (negative aspects of caregiving; positive aspects of caregiving).ConclusionThe study findings show that while grandparents recognise the value and benefits of providing regular childcare, there are important challenges that need to be addressed. It would therefore be advisable for health professionals to take into account the experience of grandparent caregivers and the process of caring for young children when developing inclusive policies for this population of caregivers.